Arthritis instantaneously causes collagen type I and type II degradation in patients with early rheumatoid arthritis: a longitudinal analysis. Issue 1 (26th August 2005) - Landewé, R B M; Geusens, P; van der Heijde, D M F M; Boers, M; van der Linden, S J; Garnero, P
Abstract : Background: Markers of collagen type I (CTX-1) and type II (CTX-II) degradation, reflecting bone and cartilage breakdown, appear to predict long term radiographic progression in chronic persistent arthritis. Objective: To analyse longitudinally whether changes in arthritis severity are linked to immediate changes in the level of CTX-I and CTX-II degradation. Methods: CTX-I and CTX-II were measured in urine samples from 105 patients with early rheumatoid arthritis who had participated in the COBRA trial at baseline and at 3, 6, 9, and 12 months after the start of treatment. The course of the biomarkers over time was compared with the course of ESR, swollen and tender joint counts, and 28 joint disease activity score (DAS28), measured at the same time points, with adjustment for rheumatoid factor, treatment, and baseline radiographic damage, by generalised estimating equations (GEE) with first order autoregression. Results: GEE showed that CTX-I was longitudinally associated with DAS28, but not with ESR, swollen joint count, or tender joint count. CTX-II, however, was longitudinally associated with ESR, swollen joint count and DAS28, but not with tender joint count. The longitudinal association implies that an increase in the extent of arthritis is immediately followed by an increase in collagen type II degradation, and to a lesser extent collagen type I degradation. Conclusions: Cartilage degradation as measured by CTX-II and to a lesser extent bone degradation as measured by CTX-I closely follows indices of arthritis. Clinically perceptible arthritis is responsible for immediate damage, which will become visible on plain x rays only much later.